Involvement of GABAergic System in Increased Pentylenetetra-zole-Induced Seizure Threshold in Cholestatic Mice: GABAergic system and PTZ-induced STin cholestasis - Khayat Nouri, Mir Hadi; Babapour, Vahab; Samini, Morteza (Iranian Journal of Pharmaceutical Sciences, 2007)
Gamma-aminobutyric acid (GABA) is an important inhibitory transmitter incentral nervous system and is involved in pathophysiology of epilepsy. Pentylenete-trazole (PTZ), a convulsant agent, partly acts via anion channel of GABAAreceptor.Ivermectin, an antiparasitic agent and a GABAAagonist, has anticonvulsant effectin animal seizure models. Cholestasis increases the threshold of PTZ-inducedclonic seizure in mice. The object of this study was to clarify the involvement ofGABAergic pathways in increasing PTZ-induced seizure threshold (ST) in cholestaticmice. The result of this study showed that cholestasis increases clonic STthree daysafter surgery while sham-operated control (SOC) and unoperated control (UOC)groups did not show any alteration in clonic ST. Bicuculline, a GABAAantagonist,reversed but ivermectin increased the clonic STin UOC, SOC and bile duct-ligatedmice, respectively. In conclusion, our results showed that: (1) acute cholestasis isassociated with an increase in PTZ-induced clonic STin mice and this phenomenonmay be the result of reinforcement of GABAergic system, and (2) GABAplays aphysiological role in regulation of ST.